2021
DOI: 10.22161/jhed.3.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility : The Influence of Employee Engagement on Corporate Social Responsibility

Abstract: Including more people being aware of corporate social responsibility, questions have arisen concerning whether there is a link between employee engagement and corporate social responsibility. Corporate Social Responsibility (CSR) is being considered as a significant component of a company's performance and activities, with the goal of increasing employee engagement. The goal of this study is to find out how employee engagement and corporate social responsibility are linked. The research was carried out in Erbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…This result is similar to findings of Chaudhary & Akhouri (2018). Mnagement can use CSR policies as strategic tool for engaging employees towards organization (Ferreira & Oliveira, 2014;Albdour & Altarawneh, 2012;Ali & Ali, 2011; ). Similarly, using data gathered from two international organizations in Greece, it is demonstrated that organizations implementing CSR policies can acheive better employees engagement and commitment (Ahmad & Islam, 2018;Tsourvakas & Yfantidou, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…This result is similar to findings of Chaudhary & Akhouri (2018). Mnagement can use CSR policies as strategic tool for engaging employees towards organization (Ferreira & Oliveira, 2014;Albdour & Altarawneh, 2012;Ali & Ali, 2011; ). Similarly, using data gathered from two international organizations in Greece, it is demonstrated that organizations implementing CSR policies can acheive better employees engagement and commitment (Ahmad & Islam, 2018;Tsourvakas & Yfantidou, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…Previous research paid more attention to attitudinal outcomes, for example; ethical leadership (De Roeck and Farooq, 2017), employee satisfaction (Ali and Anwar, 2021), organizational commitment (Gupta, 2015), organizational civility norms and job calling (Hur et al , 2018) and turnover intention (Wang et al , 2020). This study validates the suggestion that PEN and EGB initiatives enhance the strength between the firms and society.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of leadership styles on employee-driven innovation (EDI) through the prism of employee appreciation has been examined (Flocco et al, 2021). Motivation, improved performance, and developing an inventive culture inside a company depend on employee recognition (Ali & Anwar, 2021). During the COVID epidemic, Kraiger and Ford (2021) highlighted the value of social and psychological benefits in promoting employee loyalty.…”
Section: Employee Recognition Extrinsic and Intrinsic Rewardsmentioning
confidence: 99%